Null mannheim curves in the minkowski 3-space E13 - Oztekin, Handan B.; Ergut, Mahmut (Tubitak Scientific & Technological Research Council Turkey, 2011)
In this study, we give the definition of null Mannheim curve with timelike or spacelike Mannheim partner curve in the Minkowski 3-space E-1(3). We get the necessary and sufficient conditions for the null Mannheim curves. Then we investigate the null and timelike or spacelike generalized helix as the null Mannheim curve and timelike or spacelike Mannheim partner curve, respectively.
Keywords: Mannheim curve; null curve; Minkowski space